Emerging Trends of Benzotriazole Ring Cleavage (BtRC) in Organic Synthesis - Yadav, Mangal S.; Tiwari, Vinod K. (Synlett, 2025)
The distinct structural features of benzotriazole heterocycle facilitates the formation of new bonds and promotes denitrogenation processes for an easy access to physiologically relevant molecules through benzotriazole ring cleavage (BtRC) path. Several important functionalization of benzotriazole precursors have been now well established, notably the cyclization, arylation, alkenylation, alkylation, carbonylation, and the conception of carbon–heteroatom linkages. This account provides a concise overview on recent developments in the ring cleavage of N-thioacylbenzotriazoles, N-acylbenzotriazoles, N-triflylbenzotriazoles, and N-vinylbenzotriazoles under various conditions along with their growing scope in modern organic synthesis.1 Introduction2 Ring Cleavage of N-Thioacylbenzotriazoles3 Ring Cleavage of N-Acylbenzotriazoles4 Ring Cleavage of N-Trifylbenzotriazoles5 Ring Cleavage of N-Vinylbenzotriazoles6 Miscellaneous Ring Cleavage Applications7 Conclusion and Future Outlook
Keywords: benzotriazole ring cleavage (BtRC); benzotriazole; denitrogenation; functionalization